A Cross Sectional Study on Selected Dimensions of Foot in Adult Bangalee and Chakma Females of Bangladesh - Bhattacharjee, Sharmista; Ashrafuzzaman, Md; Razzaque, Laila (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Foot dimensions show variations between ethnic groups. Anthropometric study of foot dimensions of various ethnic groups is required to establish the ethnic identity of an individual. It also helps in accurate designing of workstations, equipment, footwear, orthotics, insoles, prosthetics etc.The aim of this study was to compare the foot dimensions of Bangalee and Chakma females of Bangladesh to find out their unique ethnic characteristics. Materials and methods: It was a cross sectional, observational study. Two hundred Bangalee and two hundred Chakma adult females were recruited from Chattogram city. Height and foot dimensions of the participants was taken with a measuring tape and slide caliper. Results: The foot length of Bangalee and Chakma females were 22.91 ± 0.79 cm and 23.11 ± 0.78 cm respectively. The foot breadth of Bangalee and Chakma females were 8.55 ± 0.40 cm and 9.22 ± 0.48 cm respectively. The t test showed statistically significant difference between adult Bangalee and Chakma females in terms of FL (Foot length) and FB (Foot breadth). The foot height of Bangalee and Chakma females of Bangladesh were 6.38 ± 0.55 cm and 6.32 ± 0.39 cm respectively. FH (Foot height) showed no significant difference between the ethnic groups. Conclusion: The results of this study should be useful in ergonomic design and forensic investigations. JCMCTA 2020 ; 31 (2) : 65-68